Bidirectional association between blood pressure and depressive symptoms in young and middle-age adults: A cohort study. (15th July 2020) - Jeon, Sang Won; Chang, Yoosoo; Lim, Se-Won; Cho, Juhee; Kim, Han-Na; Kim, Kyoung-Beom; Kim, Jinseok; Kim, Young Hwan; Shin, Dong-Won; Oh, Kang-Seob; Shin, Young-Chul; Ryu, Seungho
Abstract: Aims: To evaluate the bidirectional relationship between blood pressure (BP) and depressive symptoms using a large prospective cohort study. Methods: Prospective cohort study was performed in 276 244 adults who participated in a regular health check-up and were followed annually or biennially for up to 5.9 years. BP levels were categorised according to the 2017 American College of Cardiology and American Heart Association hypertension guidelines. Depressive symptoms were assessed using Centre for Epidemiologic Studies-Depression (CESD) questionnaire and a cut-off score of ≥25 was regarded as case-level depressive symptoms. Results: During 672 603.3 person-years of follow-up, 5222 participants developed case-level depressive symptoms. The multivariable-adjusted hazard ratios (HRs) [95% confidence interval (CI)] for incident case-level depressive symptoms comparing hypotension, elevated BP, hypertension stage 1 and hypertension stage 2 to normal BP were 1.07 (0.99–1.16), 0.93 (0.82–1.05), 0.89 (0.81–0.97) and 0.81 (0.62–1.06), respectively ( p for trend <0.001). During 583 615.3 person-years of follow-up, 27 787 participants developed hypertension. The multivariable-adjusted HRs (95% CI) for incident hypertension comparing CESD 16–24 and ⩾25 to CESD < 16 were 1.05 (1.01–1.11) and 1.12 (1.03–1.20), respectively ( p for trend <0.001) and in the time-dependent models, corresponding HRs (95% CI) were 1.12 (1.02–1.24) and 1.29 (1.10–1.50), respectively ( p for trend <0.001). Conclusions: In this large cohort study of young and middle-aged individuals, higher BP levels were independently associated with a decreased risk for developing case-level depressive symptoms and depressive symptoms were also associated with incident hypertension. Further studies are required to elucidate the mechanisms underlying the bidirectional association between BP levels and incident depression.